Different Roles of Environmental Selection, Dispersal, and Drift in the Assembly of Intestinal Microbial Communities of Freshwater Fish With and Without a Stomach - Zha, Yinghua; Lindström, Eva S.; Eiler, Alexander; Svanbäck, Richard (Frontiers in Ecology and Evolution, 2020)
The composition of intestinal microbiota commonly varies among animal hosts and may affect host health. However, we have limited knowledge about the different relative roles of assembly processes, such as drift, dispersal and environmental selection, for the composition of gut microbiota. Here, we conducted a field study analyzing intestinal microbial communities of two fish species that either have (perch) or lack (roach) a stomach. We used a suite of statistical tools to evaluate the role of different assembly processes for intestine microbiota, including null model analysis (Fine and Kembel, 2011; Stegen et al., 2013, Chase et al., 2011), SourceTracker analysis (Knights et al., 2011) and several multivariate analyses, such as pRDA and PLS analysis. Drift, dispersal (i.e. microbes associated with food sources) and environmental factors (i.e. diet, host habitats), appeared to be of equal importance for the assembly of intestinal microbial communities in roach, while drift appeared most important in perch, followed by dispersal and environmental selection. Furthermore, we found that microbes associated with macroinvertebrates had a positive association to fish body condition (weight/length3) whereas microbes associated with zooplankton had a negative association to fish body condition. These results emphasize the important combined roles of drift, dispersal and environmental selection in shaping the host-associated microbial communities. We conclude that general conclusions about fish as a whole are not justified since different species differ in the relative roles of these important drivers of community assembly.